My sister's keeper : a novel - Picoult, Jodi, 1966- (New York : Washington Square Press, 2005)
Conceived to provide a bone marrow match for her leukemia- stricken sister, teenage Kate begins to question her moral obligations in light of countless medical procedures and decides to fight for the right to make decisions about her own body.
"WSP readers club."
Includes a readers' club guide in the back of the book.
840
Keywords: Sisters -- Fiction; Teenage girls -- Fiction; Leukemia -- Patients -- Fiction; Organ donors -- Fiction; Sick children -- Fiction; Mothers and daughters -- Fiction; Domestic fiction